Kebijakan Pelaksanaan Vaksinasi Covid-19 Di Kota Medan Tahun 2020 - Fitriani Pramita Gurning; Laili Komariah Siagian; Ika Wiranti; Shinta Devi; Wahyulinar Atika (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2021)
Vaccination is a process in the body, where a person becomes immune or protected from a disease so if the one time exposed to the disease then it will not hurt or only experience mild pain, usually with the administration of the vaccine. Vaccination not only aims to break the chain of transmission of the disease and stop the outbreak, but also in the long term to eliminate even mengeradikasi (destroy/ eliminate) the disease itself. This research method uses a qualitative approach to obtain data descriptive with data collection techniques to study literature (literature review). According to the Department of Health of the City of Medan in the implementation of the vaccination is carried out in two stages. For the first phase of Pemko Medan receive 20,000 vaccine covid-19, where for the first stage in priority to the health workers to gradually to the community. The second stage, Pemko Medan receive 96.000 vaccine covid-19, vaccination is the second stage is also intended for public service officer including the state civil apparatus (ASN) and others. Legislation on Procurement of Vaccines and Implementation of Vaccination In the Framework of Combating the COVID-19 in the Presidential decree No. A 99-Year 2020.